Late Dorset architecture on Little Cornwallis Island, Nunavut - LeMoine, Genevieve; Helmer, James; Grønnow, Bjarne (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractLate Dorset dwellings from two sites on Little Cornwallis Island (Nunavut) illustrate the diversity of architectural forms from this period. Ten architectural features are described. They include five tent rings, ascribed to warm season occupations, and five rectangular semi-subterranean houses with axial features, including one exceptionally well-preserved example, ascribed to cold season occupations. Variations in size, number of hearths, and construction techniques are examined and the use of both types of structures to house multiple nuclear families is suggested.